Awareness of the phonetic distinctions between oral and written language mediates the connection between phonemic awareness and reading - Pittas, Evdokia (Frontiers in Education, 2025)
The aim of this study was to examine the contributions of dialect awareness in children's reading when the children use a vernacular language that differs from the form of the language in which they learn to read and write. The target group (N = 396) consisted of children, aged 6 to 9 years, who learn literacy in Cyprus using Standard Modern Greek (SMG) but who, in everyday life, use Greek Cypriot that differs from SMG in phonological features. Greek Cypriot children are exposed to oral SMG in formal settings, and it is the medium of instruction in school. Fixed order multiple regression analysis showed that dialect awareness predicted performance in the reading test over and above grade level, the estimated verbal ability and phonemic awareness. The results of the path model with phonemic awareness as the predictor variable, dialect awareness as the mediator and the reading test as the outcome variable, demonstrated that dialect awareness mediates the connection between phonemic awareness and reading. This study makes theoretical and empirical contributions to understanding the connections between oral language and reading.